STRATEGI KOMUNIKASI PEMASARAN DIGITAL LOWKY KAFE DALAM MENINGKATKAN ENGAGEMENT PADA SOSIAL MEDIA INSTAGRAM - II Tri Wahyuni; Murtiadi; Andi Banus Achir (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The development of social media has transformed the way businesses communicate with their consumers, particularly in the food and beverage industry. Instagram has become one of the primary platforms for digital communication. This study aims to analyze the digital communication strategy implemented by lowky in increasing audience engagement through Instagram. This research employed a descriptive qualitative approach. Data were collected through in-depth interviews, observation, and documentation. The research informants consisted of the Social Media Admin as the key informant, the Head Bar, the Head Kitchen, and customers as supporting informants. The findings indicate that lowky implements its digital communication strategy through structured content planning, audience-oriented message development, and the utilization of Instagram features such as reels, stories, feeds, and highlights. The uniqueness of lowky’s digital communication strategy lies in its storytelling approach through the Si Manis Americano content series, which combines cinematic storytelling with soft-selling techniques closely related to everyday life. This strategy successfully increased audience engagement through likes, comments, shares, saves, and contributed to higher customer visits as well as collaboration opportunities with influencers and other partners. The study concludes that storytelling serves as an effective digital communication strategy in strengthening audience engagement through Instagram.